2004
DOI: 10.1074/jbc.m405080200
|View full text |Cite
|
Sign up to set email alerts
|

Rad53 Kinase Activation-independent Replication Checkpoint Function of the N-terminal Forkhead-associated (FHA1) Domain

Abstract: Saccharomyces cerevisiae Rad53 has crucial functions in many aspects of the cellular response to DNA damage and replication blocks. To coordinate these diverse roles, Rad53 has two forkhead-associated (FHA) phosphothreonine-binding domains in addition to a kinase domain. Here, we show that the conserved N-terminal FHA1 domain is essential for the function of Rad53 to prevent the firing of late replication origins in response to replication blocks. However, the FHA1 domain is not required for Rad53 activation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…3D). These results are consistent with the previously proposed role for Dbf4 as a checkpoint target (21,12,39). Interestingly, it was the elimination of motif N and not motif M that had the greatest effect on the Dbf4-Orc2 interaction.…”
Section: Discussionsupporting
confidence: 92%
“…3D). These results are consistent with the previously proposed role for Dbf4 as a checkpoint target (21,12,39). Interestingly, it was the elimination of motif N and not motif M that had the greatest effect on the Dbf4-Orc2 interaction.…”
Section: Discussionsupporting
confidence: 92%
“…However, the efficient activation of late origins during recovery from DNA damage appears to result from regulation of different Rad53 phosphorylation sites by another phosphatase(s). This model is supported by work that has shown that different facets of the checkpoint response controlled by Rad53 are mediated by different domains of the protein (31)(32)(33). Additional support for this model is provided by the observation that different Rad53 residues are phosphorylated in response to different types of DNA damage (18,34).…”
Section: Discussionmentioning
confidence: 82%
“…32 P]dCTP-labeled cDNAs followed by exposure to PhosphorImager screens (Molecular Dynamics) as described previously (49,50). In all cases, ϳ500-bp gene-specific probes were amplified by PCR, cloned into pGEM-T, confirmed by sequencing, and gel purified after restriction endonuclease digestion before labeling.…”
Section: Methodsmentioning
confidence: 99%
“…Mec1 and Tel1 phosphorylate a large number of effectors, preferentially on SQ or TQ residues that are often concentrated in SQ/TQ cluster domains, in order to propagate the checkpoint signal (64). An important substrate is the Chk2-like protein kinase Rad53, which plays a crucial role in signal amplification and whose phosphorylation state is a widely used marker for general checkpoint activity (30,46,49,50,55). In case of very limited irreparable DNA damage (a single DSB in wild-type cells), checkpoint signals are eventually inactivated such that cells can adapt to persistent damage and resume proliferation until loss of the damaged chromosome leads to loss of viability (46).…”
mentioning
confidence: 99%